Development outreach : putting knowledge to work for development - World Bank Institute (Washington,D.C World Bank, 1999)
WB elibrary: "Development Outreach was designed to occupy the middle ground between scholarly journal and general interest magazine, and it presented a range of viewpoints from renowned authors and specialists worldwide. Articles on complex topics were written to be accessible to the general reader. Articles were reviewed by an international editorial board culled from the private sector, development community at large, and academia.
From 1999 published three time a year and from 2009 to 2011 published two or three times a year. The library has 2 copies of vol. 6 (2004), 7(2005), 8 (2006).
Keywords: Economic development; ECONOMIC DEVELOPMENT; PERIODICALS